Liminalität und Adoleszenz Victor Turner, Mukanda und die Psychoanalyse oder: the anthropologist's fallacy. - Claucig, Christian (Turia und Kant, 2016)
Based upon the description of the psychoanalytic subtext in the work of Victor Turner, his concept of structure and antistructure is submitted to a fundamental revision.